Sea buckthorn and its flavonoids isorhamnetin, quercetin, and kaempferol favorably influence bone and breast tissue health - Martiniakova, Monika; Penzes, Noemi; Biro, Roman; Sarocka, Anna; Kovacova, Veronika; Mondockova, Vladimira; Ciernikova, Sona; Omelka, Radoslav (Frontiers in Pharmacology, 2024)
Bone tissue and breast tissue are interrelated, as demonstrated by breast microcalcifications, breast cancer bone metastases, bone morphogenetic proteins, and Wnt signaling. In addition, osteoblasts and osteoclasts represent an important switch of tumor cell dormancy during bone metastasis. Damage to both types of tissues mentioned above is highly prevalent, especially in postmenopausal women, and manifests itself in osteoporosis and breast cancer. Sea buckthorn (Elaeagnus rhamnoides L.), a botanical drug with high antioxidant, antitumor, anti-inflammatory, immunomodulatory, and regenerative properties, has great therapeutic potential due to the unique composition of its bioactive metabolites. This review aimed to summarize the current knowledge from in vitro and in vivo studies on the effect of sea buckthorn, as well as its most widespread flavonoids isorhamnetin, quercetin, and kaempferol, on bone and breast tissue health. In vitro studies have revealed the beneficial impacts of sea buckthorn and aforementioned flavonoids on both bone health (bone remodeling, mineralization, and oxidative stress) and breast tissue health (cancer cell proliferation, apoptosis, tumor growth, and metastatic behavior). In vivo studies have documented their protective effects against disturbed bone microarchitecture and reduced bone strength in animal models of osteoporosis, as well as against tumor expansion and metastatic properties in animal xenograft models. In any case, further research and clinical trials are needed to carefully evaluate the potential therapeutic benefits of sea buckthorn and its flavonoids. Based on the available information, however, it can be concluded that these bioactive metabolites favorably affect both bone and breast tissue health.